2002
DOI: 10.1038/sj.ijir.3900892
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of erectile dysfunction in Salvador, northeastern Brazil: a population-based study

Abstract: Our objectives were to determine the prevalence of erectile dysfunction (ED) in Brazil and to explore potential sociodemographic, medical, and lifestyle correlates. A cross-sectional, populationbased, household survey was conducted in Salvador, Bahia, Brazil. Cluster samples of representative households were randomly selected for interviews. Of 654 eligible subjects, 602 (92%) participated. A structured questionnaire was administered by trained interviewers. ED was categorized as 'none', 'mild', 'moderate', or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
13

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 27 publications
5
57
1
13
Order By: Relevance
“…The most common concomitant illnesses were hypertension and diabetes mellitus, with the most common concomitant medications being antihypertensive drugs and antidiabetic drugs. This observation is consistent with the identification of hypertension and diabetes and associated drug treatments as significant correlates of ED in the epidemiological studies conducted in Brazil 8 and the northern countries of South America (Colombia, Ecuador, Venezuela), 6 as well as in other epidemiological studies. 9 Consistent with the identification of vascular disease as a risk factor for ED, 10 approximately 7% of all patients had underlying ischemic heart disease.…”
Section: Concomitant Medical Conditions and Medicationssupporting
confidence: 75%
“…The most common concomitant illnesses were hypertension and diabetes mellitus, with the most common concomitant medications being antihypertensive drugs and antidiabetic drugs. This observation is consistent with the identification of hypertension and diabetes and associated drug treatments as significant correlates of ED in the epidemiological studies conducted in Brazil 8 and the northern countries of South America (Colombia, Ecuador, Venezuela), 6 as well as in other epidemiological studies. 9 Consistent with the identification of vascular disease as a risk factor for ED, 10 approximately 7% of all patients had underlying ischemic heart disease.…”
Section: Concomitant Medical Conditions and Medicationssupporting
confidence: 75%
“…Our initial search identified 221 articles, but only 11 cross-sectional studies [13][14][15][16][17][18][19][20][21][22] documented the adjusted OR for alcohol, another cross-sectional study 23 and a prospective cohort 24 from the same study population provided adjusted relative risks (RR), one cohort study 25 provided adjusted OR. Only the 11 cross-sectional studies that provided adjusted ORs will be included in the meta-analysis, since the other two cohort studies were of different study design, and the RR reported by the cross-sectional and cohort studies were derived with a different statistical method (Mantel-Haenszel rather than logistic regression).…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol consumption and erectile dysfunction JYW Cheng et al (95% CI, 12-22), 16% (11-23) and 15% (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) in those with o1 drink/day, 1-3 drinks/day and X4 drinks/day of alcohol consumption respectively. This incidence figure was adjusted for age, active and passive smoking, overweight, hypertension, physical activity, cholesterol, fat intake, testosterone, depression and antihypertensive medication intake.…”
Section: Cohort Study (Mmas)mentioning
confidence: 99%
“…Most of these studies have involved the populations of industrially developed nations around the world, particularly in Europe, [1][2][3] and in the Americas. [4][5][6][7][8][9][10][11][12] The prevalence of the male sexual problems of erectile dysfunction and early ejaculation and their related risk factors have been investigated most extensively, whereas fewer studies have focused specifically on female sexual dysfunction. 13,14 Moreover, relatively little is known about the average frequency of sexual activity and the importance of sexual relationships among older men and women, although the few studies that have examined sexuality in mature adults have reported that sexual interest and activity persist well into older age.…”
Section: Introductionmentioning
confidence: 99%